Recent 3D and 4D intelligent printing technologies: A comparative review and future perspective - Ma, Quanjin; Rejab, M. R. M.; Idris, Mat Sahat; Manoj Kumar, Nallapaneni; Abdullah, M. H.; Reddy, Guduru Ramakrishna (Elsevier, 2020)
Additive manufacturing (AM) is generally recognized as three-dimensional (3D) printing or raPID prototyping, which has evolved raPIDly in numerous applications. In recent years, a new term has emerged as four-dimensional (4D) printing, which utilizes additive manufacturing methods to print stimulus-responsive products subjected to specific stimuli. 4D printing is generally regarded as the further evolution of 3D printing. In this review paper, recent major fundamentals and technology development between 3D and 4D printing are reviewed, including its features and latest findings. Comparative analysis and rating level are further compared and analyzed using SWOT analysis method. Moreover, some potential applications between 3D and 4D printing are involved, followed by its typical applications, advance trend, and future perspective.